BITTER HERBS OF EASTERN NIGERIA (GONGRONEMA LATIFOLIUM, VERNONIA AMYGDALINA AND VITEX DONIANA): A REVIEW - Chinwe U., Asuzu (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: The article is a review of three bitter vegetables consumed in South-eastern Nigeria (Gongronema latifolium, Vernonia amygdalina and Vitex doniana). These vegetables are not very palatable to taste but are highly famed because of the myriad of illnesses that they are reputed to cure and manage. The different aspects of these vegetables reviewed are their ethnobotany, zoo pharmacology, bioactivity, phytochemistry and toxicity. Materials and method: The literatures consulted were searched using electronic search engines (Google, Google scholar and Pubmed). Substantial amount of literature was consulted but only those directly related to the main review were selected. Result: The review revealed that the three bitter vegetables possessed phytochemicals like saponins, flavonoids, alkaloids among others that justify the claims of curing and managing many of the illnesses that traditional folks attribute to them. From literature, antimicrobial, antinflammatory, antidiabetic, antioxidant and anti cancer activities were attributed to these three bitter herbs. Antinutritional substances like phytate and oxalate reported in these herbs were not regarded as harmful for human consumption because of the traditional method of processing the vegetables by squeeze washing in several changes of water. Conclusion: The three bitter herbs are regarded as beneficial for human consumption and the information should be disseminated to a large audience. Key words: V. amygdalina, V. doniana, G.